Gotowość studentów z dysleksją do komunikowania się w językach obcych - Klapa, Julia (Neofilolog, 2023)
The study concerns in a group of young adults (students) with dyslexia as dyslexia may be a factor that differentiates the assessments and declarations of the respondents in this area. The aim is to show the factors important for shaping the willingness to communicateof students with and without dyslexia. The theoretical basis is the analysis of selected aspects of teaching to and learning of foreign languages by adults with dyslexia and willingness to communicate in foreign languages, shaped by the personal characteristics of the language user and the educational process. The empirical part presents the methodological basis of the research and results obtained in a group of 263 students. Conclusions and recommendations for academic practice are drawn on the basis of the results of the research project.